2017
DOI: 10.1093/aob/mcx103
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional signals in gymnosperm ovular secretions

Abstract: Chemical profiles of ovular secretions of ambophilous gymnosperms show a clear signal of pollinator-driven selection, including higher levels of carbohydrates than anemophilous taxa, lower levels of amino acids, and the presence of specific amino acids, such as β-alanine, that are known to influence insect feeding behaviour and physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 88 publications
1
73
0
Order By: Relevance
“…Of the four major lineages of current gymnosperms, wind pollination is the exclusive pollination mode in extant conifers and Ginkgo (Nepi et al, 2017), whereas insects overwhelmingly are pollinators of cycads and gnetaleans (Labandeira, 2010;Ickert-Bond and Renner, 2016). For the latter, pollinator assemblages vary in their specialization and range from near-obligate mutualisms in some cycads to eclectic, generalized associations in almost all gnetaleans (Labandeira et al, 2007;Nepi et al, 2017). Most seed-plant species are visited by taxonomically diverse groups of pollinators, and pollinator species overwhelmingly visit several or more plant species (Waser et al, 1996).…”
Section: Evolution Of the Pollination Mutualism Between Insects And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four major lineages of current gymnosperms, wind pollination is the exclusive pollination mode in extant conifers and Ginkgo (Nepi et al, 2017), whereas insects overwhelmingly are pollinators of cycads and gnetaleans (Labandeira, 2010;Ickert-Bond and Renner, 2016). For the latter, pollinator assemblages vary in their specialization and range from near-obligate mutualisms in some cycads to eclectic, generalized associations in almost all gnetaleans (Labandeira et al, 2007;Nepi et al, 2017). Most seed-plant species are visited by taxonomically diverse groups of pollinators, and pollinator species overwhelmingly visit several or more plant species (Waser et al, 1996).…”
Section: Evolution Of the Pollination Mutualism Between Insects And Pmentioning
confidence: 99%
“…Crepet and Friis (1987) supported the hypothesis that insect pollination evolved from Carboniferous seed ferns and subsequently was extended to Bennettitales during the Jurassic and then to magnoliacean (magnolias) and annonacean (custard apples) angiosperms in the Early Cretaceous. Gymnosperm pollen or secretions like the pollination drops fed insects as awards initially (Grimaldi, 1999;Labandeira, 2010;Nepi et al, 2017). Long-proboscid mouthpart structures known from the Mesozoic required deep-throated receiving structures in ovulate organs of gymnosperms; the bowlshaped flower structure of early angiosperms likely was pollinated by unspecialized, small, mandibulate insects such as beetles (Dilcher, 2000;Endress and Igersheim, 2000;Wang et al, 2013;Labandeira et al, 2016;Lin et al, 2019).…”
Section: Evolution Of the Pollination Mutualism Between Insects And Pmentioning
confidence: 99%
“…When the ovule is receptive for pollination, a pollination drop is secreted and exudes through the micropyle. Pollen is delivered to the ovule by wind, or by insects in the case of some cycads (Terry et al 2005 ) and Gnetales (Kato 1994 ), and possibly in Ginkgo (Nepi et al 2017 ). Pollination drop and pollen then meet, and pollen is carried through the micropyle as the pollination drop recedes.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis further determined that total soluble sugar was present at approximately 5.9%, which was a higher content than that of other anemophilous gymnosperms (1-2%), 4 but lower than G. biloba reported by Nepi et al (34.7 ± 8.1%). 12 The reason for the low sugar content in our study may be because of the collection of PDs in relatively humid conditions. In most anemophilous gymnosperm ovular secretions, fructose tends to be the dominant sugar; 1 however, in G. biloba PDs, the glucose content was higher than that of fructose, and the sucrose concentration was the lowest.…”
Section: Discussionmentioning
confidence: 77%
“…11 Recent research has also identified serine, glutamic acid, glycine, histidine, alanine, and proline, which have been shown to be abundant in the ovular secretions of numerous gymnosperms, including Ephedra minuta, Zamia furfuracea, Cephalotaxus koreana, Chamaecyparis lawsoniana, and T. baccata. 12 With the application of proteomics technologies, functional proteins have been detected in the PDs of several gymnosperms. [13][14][15] The proteins detected in PDs can be divided into five categories: (1) those involved in the modification of sugars, e.g., xylosidase and galactosidase, 13 (2) those serving a defense-like function, e.g., glucan-β-1,3-glucosidase, chitinase, and thaumatin-like protein, [14][15][16] (3) those associated with the freeze-proofing function, 17 (4) those associated with plant cell metabolism, e.g., peroxidase, 18 and (5) those capable of accelerating pollen tube growth, e.g., aspartyl protease and serine carboxypeptidase.…”
Section: Introductionmentioning
confidence: 99%